Evangelical attitudes toward Syrian refugees: are evangelicals distinctive in their opposition to Syrian refugees to the United States? - Roy, Oindrila (Politics and religion, 2023)
This study analyzes a potential source of immigration policy by comparing attitudes toward Syrian refugees across different religious traditions in the United States. The analysis focuses on the puzzling case of evangelical public opinion, where the views of lay evangelicals showed a contrast with the pro-refugee stance of the church leadership. The current analysis examines the sources of evangelical public opinion by scrutinizing the mediating effects of Muslim stereotypes. The findings from a series of regression analyses using the ANES dataset (2016) suggest that while evangelicals are not distinctive in their opposition to Syrian refugees, they are unique in holding significantly high levels of Muslim stereotypes, which makes them more opposed to allowing refugees from Syria. Additionally, interesting differences in attitudes emerge within the evangelical community, thereby cautioning against generalizing the divide between church leadership and laity. Finally, measures of religiosity demonstrate significant effects on attitudes across religious traditions.